Analysis of the Lavani Volleyball Team's Offense in the 2026 Proliga Tournament - Reyhan Alpha Rizky Dhani Pradhana; Aziz Amrulloh Aziz Amrulloh (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to analyze the effectiveness of the Lavani volleyball team’s of-fensive variations during the Final Four through the Grand Final of the 2026 Pro-liga. The study employs a quantitative descriptive method with an ex post facto approach. The research sample was determined using purposive sampling, data were collected through indirect observation by analyzing video recordings and official match statistics using an observation sheet. The variables analyzed in-cluded the serve, open spike, back attack, and quick attack. The results of the study show that the total number of attack attempts by the Lavani team reached 1,135. The serve was the most dominant technique with 530 successful attempts, 113 errors, and 39 aces, achieving an effectiveness rate of 82.43%. The open spike recorded an effectiveness rate of 79.92% with 215 successful attempts and 54 errors. The back attack had the highest effectiveness rate of 86.32% with 101 suc-cessful attacks and 16 errors, while the quick attack showed an effectiveness rate of 84.91% with 90 successful attacks and 16 errors. Based on these results, it can be concluded that the Lavani team possesses excellent attacking quality with a variety of effective, organized, and difficult-to-anticipate attack patterns.